Gasto maior do que o necessário com telefonia celular: existência e motivos de vieses na escolha de plano tarifário no Brasil - Harada, Carlos André Nascimento (2007)
The Brazilian cell phone companies make available several plans of post paid services with non-linear rates. The users, however, not always choose that one that reduces their expenses: i) some users have inferior use than the one that their plan offers, and they would spend less if they adopted a plan of smaller franchise ('flat-rate ' bias); ii) others use more minutes than their plan offers, and they would spend less if they adopted a plan of larger franchise ('pay-per-use' bias). For the specific context of the services of a cell phone company and region of Brazil, this dissertation had as aim to identify these inclinations and their potential explanations. The diagnosis of the inclinations was made starting from the analysis of the transactions data of minutes use and plans chosen by the consumers. The inclinations are present in most to the of the users choice, being the 'pay-per-use' bias as frequent as the 'flat-rate' bias. The first ones represent a challenge for the cell phone companies, because they have a profile of use and spendings above the base average, but a lack of loyalty to the company greatly rewards the prize for the price paid due to the bias. Those with 'flat-rate' bias, although with lower use and spendings, not only incur into cost above the necessary but also are more loyal to the company. The investigation of the explanations of the bias used binomial logistic models, whose explanatory variables were five behavioral effects, information gathered through a survey conducted by telephone with the users of the companies: Taximeter, Convenience, Insecurity, Underestimation and Overestimation of the Use. The Convenience and Insecurity do not explain the occurrence of biases. The Overestimation of the Use is related to the 'flat-rate' bias, and the Underestimation of the Use and Taximeter are related to the 'pay-per-use' bias.